THE ENHANCEMENT OF ABILITY SELF REGULATION THROUGH OUTBOUND PLAY ACTIVITIES (AN ACTION RESEARCH IN GROUP B PAUD TAMAN BANGSA, GUNUNGSARI, WEST LOMBOK 2023) - Muhajirin, Muhammad; Alawiyah, Tuti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to describe the processes and outcomes of learning to use outbound activities play in improving children's ability to self-regulation. The model used in this study is a model Kemmis and Taggart to the study subjects were 15 children in group B PAUD Taman Bangsa, Gunungsari. The study was conducted from November 2023 to January 2023. The study was carried out in 16 meetings that are divided into two cycles. Data collected through observation, interviews and documentation. Data analysis techniques used in this research is the analysis of qualitative and quantitative data. Quantitative data analysis used to determine the percentage increase in the ability of self-regulation of children after the action. Qualitative analysis is used to explain the study results. The results showed an increase in the ability of self-regulation in children after learning followed using outbound play activities. The ability of self-regulation of children in pre-cycle equal to 56.90%. In one cycle of increased 73.45% and increased to 88.53% in cycle two. The process of playing outbound activities have an impact on various aspects of child development as follows: physical, cognitive, language, social and emotional. The implication of this research is the process of early childhood learning need to use strategy to play outbound activity can be considered as a medium to improve the child's ability to self-regulation.